Compact TiO2 layer by UV-assisted TiBr4 chemical bath deposition for perovskite solar cells. (July 2023) - Pylnev, Mikhail; Rezende Santos, Felix; Zhang, Di; Alawadhi, Hussain; Tabet, Nouar
Abstract: A new method to prepare a compact TiO2 layer for perovskite solar cells is introduced. The method features a UV-assisted chemical bath in an aqueous TiBr4 solution. The process does not require sophisticated systems to implement making scaling-up easy and the precursor ensures a uniform TiO2 layer with densely-packed planar grains. UV light provides an alternative to the temperature-assisted CBD process and eliminates the necessity to stir the solution during a deposition that opens new horizons for further scaling up PSCs. The new compact layer was compared to the spin-coated TiO2 layer and it was found that the novel method allows obtaining a more uniform layer with conformal coverage of the substrate. The new TiO2 layer was tested for perovskite solar cells and showed an improvement in open-circuit voltage (VOC ) which can be explained by improved morphology and surface coverage of the TiO2 layer. Graphical abstract: Image 1